SOSIALISASI PENGGUNAAN LEAFLET DALAM PENINGKATAN PEMAHAMAN PENGGUNAAN OBAT HERBAL UNTUK PENYAKIT KRONIS DI KOTA DENPASAR - Arimbawa, Eka (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
The instability between the success and failure of herbal treatment for chronic diseases illustrates the lack of understanding in society. For this reason, it is necessary to provide socialization of knowledge about herbal medicines through leaflets that are practical, simple, and easy to accept. This activity targets the people of Denpasar City who suffer from chronic diseases and use herbal medicines. The method used is in discussions with respondents who have or are currently undergoing degenerative disease therapy by utilizing herbal medicines as therapy and distributing leaflets containing information on herbal medicines to respondents who are less precise in understanding herbal medicines. The results of community service, giving handouts to the community, can increase knowledge about herbal treatments for chronic diseases. The use of leaflets can increase understanding of herbal medicines about the content, seek information from doctors/pharmacists as a complementary therapy, and different effects of conventional drugs. Thus, leaflets are essential to increase the rational use of medicines, especially herbal medicines.